The Kalahari typing school for men - McCall Smith, Alexander, 1948- (McCall Smith, Alexander, 1948- No. 1 Ladies Detective Agency series., 2002)
We find Precious Ramotswe, the founder of Botswana's only detective agency now running her business from the garage of her fiance, that most gracious of men, Mr J.L.B. Matekoni. Having recovered from his illness, Mr J.L.B. Matekoni is back at the helm of Tlokweng Road Speedy Motors, and plans for the couple's wedding need to be made. But when, If ever, will they wed? Intriguing cases present themselves and Mma Ramotswe juggles new clients with her usual formidable talent, but things become unusually complicated when her first-class assistant Mma Makutsi decides to expand the agency by opening a much-needed typing school for men. Amongst her puplis Mma Makutsl finds an admirer, but Mma Ramotswe, knowing how men are, decides to dig deeper.